2023
DOI: 10.1111/wre.12572
|View full text |Cite
|
Sign up to set email alerts
|

Weed suppression by cereals: Beyond ‘competitive ability’

Abstract: Much research on cereal-weed competition has been directed towards finding cultivars that have high 'competitive ability' with weeds. I argue that this objective is insufficient, because weed suppression is usually the result of interactions among genotype, environment and management rather than direct effects of genotype, and this limits the usefulness of competitive ability as a general concept. The clearest example of this is the effect of cereal crop density. Cultivars of wheat and maize that compete best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Effective weed suppression by a crop could be achieved at high crop density due to population crowding [31]. In the current study, we found that an increase in oat density could take advantage of size-asymmetric competition with weeds.…”
Section: Effect Of Oat Planting Density On Weed Suppression and Oat P...mentioning
confidence: 48%
“…Effective weed suppression by a crop could be achieved at high crop density due to population crowding [31]. In the current study, we found that an increase in oat density could take advantage of size-asymmetric competition with weeds.…”
Section: Effect Of Oat Planting Density On Weed Suppression and Oat P...mentioning
confidence: 48%